Influence of processing methods and exogenous selenium species on the content and in vitro bioaccessibility of selenium in Pleurotus eryngii. (15th February 2021) - Zhou, Fei; Peng, Qin; Wang, Min; Liu, Nana; Dinh, Quang Toan; Zhai, Hui; Xue, Mingyue; Liang, Dongli
Graphical abstract: Highlights: Selenium application had no significant effect on the growth of P. eryngii. The uptake ability of P. eryngii to exogenous Se was Na2 SeO3  > Se yeast > Na2 SeO4 . Both the boiling and frying treatments resulted in Se loss in P. eryngii . Frying reduced the bioaccessibility of Se in P. eryngii, while boiling enhanced it. Se yeast and boiling are the ideal Se source and cooking method for P. eryngii . Abstract: Understanding the effects of processing on the Se content and bioaccessibility in food is critical in guiding the development of Se-enriched products. In this study, Se-enriched Pleurotus eryngii was obtained by applying different Se supplements to the substrate. Selenium content and its bioaccessibility among raw and processed fruit bodies were compared. The application of exogenous Se had no significant effect on the yield of P. eryngii, while amendment Se yeast could slightly promote the growth of P. eryngii . The enrichment ability of P. eryngii among different Se supplements declined in the order of Na2 SeO3  > Se yeast > Na2 SeO4 . However, the processing treatments resulted in 6.6%–45.9% Se loss. The Se bioaccessibility of P. eryngii was 78.4%–89.7%. Frying treatment reduced Se bioaccessibility in samples, whereas boiling treatment enhanced it. Therefore, Se yeast and boiling treatment are recommended as the ideal Se supplement and processing method for Se-enriched P. eryngii .